Meningkatkan Minat Belajar Bahasa Indonesia Peserta Didik Melalui Pembelajaran Berbasis TPACK - Atriana, Anita; Santosa, Pratama Bayu; Hajija , Hajija (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
This study aims to enhance the motivation and learning interest of eighth-grade students at SMP Negeri 15 Palu in Indonesian language subjects through the implementation of the TPACK (Technological Pedagogical Content Knowledge) model. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 30 students of class VIII B, consisting of 15 male and 15 female students. Data were collected through observation, motivation questionnaires, and achievement tests. The findings revealed a significant improvement. In the pre-cycle, only 23% of students achieved mastery with low motivation. After applying TPACK in the first cycle, mastery increased to 50% with moderate motivation, and in the second cycle, it reached 90% with high motivation. This improvement was also reflected in students’ active participation during discussions and their ability to analyze speech texts based on local culture. Therefore, the implementation of TPACK proved effective in creating interactive and meaningful learning while improving students’ motivation and learning outcomes.